Developing a Nahwu Module Using a Self-Directed Learning Approach for Beginner-Level Learners - Bahy, Moh. Buny Andaru; Arifin, Ahmad; Saputra, Firman Cahaya; Vetiana, Gautama Veri; Abdullah (UIN Syekh Wasil Kediri, Indonesia, 2025)
Abstract: Difficulties in understanding Arabic grammar materials are commonly experienced by students due to the complexity of Nahwu content in instructional materials. This phenomenon leads to a lack of comprehension and low academic achievement. This study aims to develop a Nahwu learning module using a self-directed learning approach to help students better understand Nahwu concepts. This research adopts a Research and Development (R&D) design using the ADDIE development model. The study was conducted at Madrasah Tsanawiyah Attanwir Bojonegoro. After completing all development stages, the study produced a Nahwu learning module based on a self-directed learning approach. The developed module has been validated by subject matter and media experts. In practice, the Nahwu module has proven effective in improving students' understanding of Arabic grammar independently, as it features well-structured content that is easy for students to grasp. Abstrak: Kesulitan memahami materi gramatika bahasa Arab sering terjadi di kalangan siswa karena sulitnya memahami materi dalam bahan ajar Nahwu. Fenomena ini berdampak pada kurangnya pemahaman dan hasil belajar siswa. Penelitian ini bertujuan untuk mengembangkan modul pembelajaran Nahwu menggunakan pendekatan pembelajaran mandiri, agar siswa dapat memahamami materi nahwu dengan baik. Penelitian ini berenis penelitian R&D dengan langkah pengembangan ADDIE. Penelitian ini dilakukan di Madrasah Tsanawiyah Attanwir Bojonegoro. Setelah melakukan seluruh tahapan pengembangan, penelitian menghasilkan produk modul pembelajaran Nahwu dengan menggunakan pendekatan pembelajaran mandiri. Modul yang dikembangkan telah melalui uji validasi oleh ahli materi dan media. Dalam penerapannya, modul Nahwu ini efektif untuk meningkatkan pemahaman gramatika bahasa Arab siswa seacara mandiri, karena modul pembelajaran Nahwu ini memiliki karakteristik materi yang terstruktur dan mudah dipahami oleh siswa.